Are beta-blockers effective for preventing post-coronary artery bypass grafting atrial fibrillation? Direct and network meta-analyses. (May 2016) - Ji, T.; Feng, C.; Sun, L.; Ye, X.; Bai, Y.; Chen, Q.; Qin, Y.; Zhu, J.; Zhao, X.
Abstract Background Atrial fibrillation is the most common arrhythmia in clinical practice and is a major contributor to mortality. Recently, several studies have reported different results for treatments aimed at reducing the risk of postoperative AF. Aims The aim of this study was to evaluate the efficacy of beta-blockers (BBs) in preventing post-coronary artery bypass grafting (CABG) AF and to compare the efficacies of different BB treatments using a network meta-analytical approach. Methods The PubMed, EMBASE and Cochrane Library databases were searched (Jan 1995 to May 2014) to identify randomized controlled trials. Two independent investigators separately extracted the data using a seven-point scoring system to assess randomization, allocation concealment, blinding, withdrawals and dropouts. A direct meta-analysis of these randomized controlled trials was conducted. Then, six trials comparing different BB treatments for the prevention of postoperative AF were added to perform a Bayesian network meta-analysis with mixed treatment comparisons. Results Treatment with BBs was associated with a significant reduction in the postoperative incidence of AF compared with placebo/control [22.37 % compared with 34.45 %, relative risk (RR) = 0.53, 95 % confidence interval (CI): 0.37–0.75, p < 0.00001]. Conclusions The network meta-analysis revealed no significant differences among eight types of BB treatments but did provide a ranking. BB treatments could significantly reduce the occurrence of post-CABG AF. Insufficient evidence was available to show that one BB treatment was more effective than the others were. According to our network meta-analysis, bisoprolol and landiolol+bisoprolol are better alternatives compared with the other treatments.